Novel Crashworthy Device for Pier Protection from Barge Impact - W. Wang; G. Morgenthal (Advances in Civil Engineering)
Barge impact is a potential hazard for bridge piers located in navigation waterways. Protective structures of different types, for example, dolphin structures, artificial islands, and guiding structures, have been widely used in bridge designs against barge impact. However, such structures often imply high cost and suffer from difficulties in installation as well as maintenance challenges. This paper aims to devise and investigate a new type of crashworthy device which is comprised of vertically supported impact cap connected to the bridge pier using a series of steel beams in a frame-type arrangement. This sacrificial steel structure is designed to form plastic hinges for energy dissipation whilst limiting the force transmitted to the protected pier. The dynamic analysis of the proposed crashworthy device subjected to barge impact is conducted using a simplified impact model previously developed by the authors. The parametric studies in this paper show that the proposed device has a large energy dissipation capacity and that the magnitude of impact force transmitted to the bridge pier can be dramatically reduced. In addition, an optimization model is proposed in this paper to achieve the cost-optimized design of the crashworthy device for a given impact scenario with constraints as per the prescribed design requirements.